Parallaxes of Southern Extremely Cool objects III: 118 L and T dwarfs. Issue 3 (14th September 2018) - Smart, R L; Bucciarelli, B; Jones, H R A; Marocco, F; Andrei, A H; Goldman, B; Mendez, R A; d'Avila, V A; Burningham, B; Camargo, J I B; Crosta, M T; Daprà, M; et al.
ABSTRACT: We present new results from the Parallaxes of Southern Extremely Cool dwarfs program to measure parallaxes, proper motions and multiepoch photometry of L and early T dwarfs. The observations were made on 108 nights over the course of 8 yr using the Wide Field Imager on the ESO 2.2m telescope. We present 118 new parallaxes of L and T dwarfs of which 52 have no published values and 24 of the 66 published values are preliminary estimates from this program. The parallax precision varies from 1.0 to 15.5 mas with a median of 3.8 mas. We find evidence for two objects with long term photometric variation and 24 new moving group candidates. We cross-match our sample to published photometric catalogues and find standard magnitudes in up to 16 pass-bands from which we build spectral energy distributions and H–R diagrams. This allows us to confirm the theoretically anticipated minimum in radius between stars and brown dwarfs across the hydrogen burning minimum mass. We find the minimum occurs between L2 and L6 and verify the predicted steep dependence of radius in the hydrogen burning regime and the gentle rise into the degenerate brown dwarf regime. We find a relatively young age of ∼2  Gyr from the kinematics of our sample.